Formononetin attenuates monocrotaline-induced pulmonary arterial hypertension via inhibiting pulmonary vascular remodeling in rats - Cai, Changhong (Mol Med Rep, 2019)
Pulmonary arterial hypertension (PAH) is a life-threatening disease induced by the excessive proliferation and reduced apoptosis of pulmonary artery smooth muscle cells (PASMCs). Formononetin (FMN) is a natural isoflavone with numerous cardioprotective properties, which can inhibit the proliferation and induce the apoptosis of tumor cells; however, whether FMN has a therapeutic effect on PAH remains unclear. In the present study, PAH was induced in rats with monocrotaline (MCT, 60 mg/kg); rats were then administered FMN (10, 30 or 60 mg/kg/day). At the end of the experiment, hemodynamic changes, right ventricular hypertrophy and lung morphological characteristics were evaluated. α-smooth muscle actin (α-SMA), proliferating cell nuclear antigen (PCNA), and TUNEL were detected by immunohistochemical staining. The expression of PCNA, Bcl-2-associated X protein (Bax), Bcl-2 and, cleaved caspase-3, and activation of AKT and ERK were examined by western blot analysis. The results demonstrated that FMN significantly ameliorated the right ventricular systolic pressure, right ventricular hypertrophy, and pulmonary vascular remodeling induced by MCT. FMN also attenuated MCT-induced increased expression of α-SMA and PCNA. The ratio of Bax/Bcl-2 and cleaved caspase-3 expression increased in rat lung tissue in response to FMN treatment. Furthermore, reduced phosphorylation of AKT and ERK was also observed in FMN-treated rats. Therefore, FMN may provide protection against MCT-induced PAH by preventing pulmonary vascular remodeling, potentially by suppressing the PI3K/AKT and ERK pathways in rats.